Patterns of CSF Inflammatory Markers in Non-demented Older People: A Cluster Analysis - Peng, Yangdi; Chen, Bin; Chi, Lifen; Zhou, Qiang; Shi, Zhenjing; , The Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Aging Neuroscience, 2020)
Objective: Accumulating evidence has suggested that neuroinflammation plays a pivotal role in the pathogenesis of Alzheimer's disease (AD). In this study, we aimed to examine if patterns of CSF inflammatory markers are correlated with global cognition, episodic memory, hippocampal volume, and CSF AD-related pathologies among non-demented older people.We included 217 non-demented older individuals, including 87 subjects with normal cognition (NC) and 130 subjects with mild cognitive impairment (MCI) from the Alzheimer's Disease Neuroimaging Initiative (ADNI) study. Hierarchical cluster analysis including nine inflammatory markers in CSF [Tumor necrosis factor-α (TNF-α ), TNF-R1, TNF-R2, transforming growth factor-β1 (TGF-β1), TGF-β2, TGF-β3, Interleukin -21 (IL-21), IL-6, and IL-7] was conducted.We identified two clusters among non-demented older people based on nine inflammatory markers in CSF. Compared to the first cluster, the second cluster showed significantly higher levels of CSF inflammatory markers ((TNF-R1, TNF-R2, TGF-β1, TGF-β 3, and IL-6)). Further, the second cluster was also associated with higher levels of t-tau and ptau levels in CSF.We observed a subgroup of non-demented older people characterized by increased levels of inflammatory markers in CSF. Further, this subgroup showed higher levels of t-tau and p-tau levels in CSF.